OPTIMIZE THE FUNCTION OF A PERSONAL COMPUTER USING PPI CARD 8255 - Hasbullah Hasbullah; Ir. M. Qomarul Huda (Jurnal Sistem Komputer, 1996)
Card PPI series serves as a liaison (interface) between a PC with equipment beyond the PC. This circuit is used as a comparator IC and IC 74LS688 8255 as the output data from microcomputer. to activate this card PPI use of assembly language programs that previously have done port initialization. IC 8255 will be active when the comparator is active (low), determine which ports are used is from the address bus A0 and A1. PPI Card With this we can make a circuit or a module outside of a PC (Personal Computer) that can be treated by using a computer program. like, moving the series of LED lights, moving the DC motor circuit.